Fatigue life assessment and fracture mechanisms of additively manufactured metal-fiber reinforced thermoplastic hybrid structures produced via ultrasonic joining - Willian S. de Carvalho; Jonathan Draper; Talina Terrazas-Monje; Athanasios Toumpis; Alexander Galloway; Sergio T. Amancio-Filho (Journal of Materials Research and Technology, 2023)
Ultrasonic Joining (U-Joining) produces through-the-thickness reinforced (TTR) hybrid joints between thermoplastics and surface-structured metals. The joining parameters were previously optimized to join additively manufactured (AM) 316L stainless steel (316L SS) and 20% short-carbon-fiber-reinforced poly-ether-ether-ketone (PEEK-20CF) to maximize the joints' performance under quasi-static lap shear testing. However, further investigations on the joint's fracture mechanisms and cyclic loading performance are still lacking. Therefore, this study describes the stress distributions, assesses the fracture mechanisms and evaluates the fatigue life of AM 316L SS/PEEK-20CF hybrid joints. A finite element model was developed to clarify the joints' mechanical behavior, and their fatigue performance was assessed under cyclic tensile condition. The fatigue tests were performed at different percentages of the reached ultimate lap shear force (ULSF) and analyzed via two-parameter Weibull distribution and load-life curves for different reliability levels. The results showed that a fatigue life of 1 × 106 cycles could be reached when a load of 1.52 kN, or 42% of the ULSF, is applied, demonstrating the joints' high mechanical performance and potential for engineering applications. Joints reaching the one million cycles threshold were stopped at this mark and tested under quasi-static lap shear to assess their residual force. The results significantly decreased from 3.6 ± 0.3 kN to 2.4 ± 0.5 kN for ULSF and residual force, respectively. Fractography analyses identified polymer delamination, partial TTR pull-out, and interfacial/net-tension failure as the main fracture mechanisms. Polymer detachment in fatigue specimens indicated the influence of secondary bending at low load levels, explaining the reduced residual force.